Understanding the Economics of Orbital Pollution Through the Lens of Terrestrial Climate Change. (February 2022) - Adilov, Nodir; Alexander, Peter; Cunningham, Brendan
Abstract: Orbital space is an economically and socially valuable resource that provides a vast array of satellite communication services for consumers, businesses, scientists, and governments. Among the socially valuable services provided, orbital satellites collect various types of environmental data relating to the earth's surface and atmosphere. These data help scientists monitor and better understand the evolving terrestrial environment. When satellites are launched and undertake missions in orbital space, they create pollution in the form of orbital debris. Orbital debris can, and does, damage or destroy other satellites. National entities that use orbital space pledge to follow voluntary guidelines for minimizing orbital debris, but many do not comply. This noncompliant behavior, along with a substantial increase in the number of satellites in orbit, causes the density of the debris fields in orbit to increase, making it more likely that an increasing number of other satellites will be damaged or destroyed. The limiting case of this process is a "collisional cascade, " which renders an orbit unusable. This scenario is broadly analogous to the effects of human-produced CO2, both in terms of the increasing economic and social costs of environmental damage over time and the difficulty in binding nations to international agreements. Because satellites are vital to monitoring terrestrial conditions and provide unique data on the current state of the global environment, we suggest there is a natural linkage for including orbital space in climate change negotiations. Although this might complicate climate change negotiations, we demonstrate how it could also usefully expand the overall bargaining space, providing new opportunities for agreement.